Screening and selection of potential probiotic strains from the Mediterranean fruit fly (Ceratitis capitata) guts origin based on SIT application. Issue 1 (1st January 2020) - Hamden, H.; MSaad Guerfali, Meriem; Charaabi, K.; Djobbi, W.; Fadhl, S.; Mahjoubi, M.; Mnasri, K.; Najjari, A.; Saidi, M.; Chevrier, C.; Cherif, A.
ABSTRACT: The Mediterranean fruit fly, Ceratitis capitata  (Diptera: Tephritidae), is an important economic pest worldwide causing direct crop damage. One of the most successful control strategies for this pest is the application of the sterile insect technique. However, the deterioration of competitive mating performance against wild males was observed in Vienna8 Genetic Sexing Strain sterile males, which was aconsequence of irradiation. Therefore, beneficial probiotics were investigated to use as supplementation in sterile insect diets with properties on sexual performance enhancing which was the objective of the study. Hence, bacterial strains were isolated from  C. capitata  wild strain guts and were identified using the 16S-23S rRNA internal transcribed spacers region and 16S rRNA sequencing method. The isolated strains were evaluated for their probiotic potential by ' in vitro ' and ' in vivo ' tests. Finally, the candidate probiotic strains were selected by statistical analysis of their ' in vitro ' and ' in vivo ' tests data using principal component analysis (PCA). In conclusion, the combination of the two PCAs allowed the selection of  Enterobacter  sp.,   Lactococcus lactis  and  Klebsiella oxytoca  as potential probiotic candidates to integrate into the larval diet.